APPRAISING THE NECESSARY PLACE OF ETHICS IN THE DIFFERENT DOMAINS OF EDUCATION - Kani, Umar Mohammed; Rashid, Rabiatul-Adawiah Ahmad (Sokoto Educational Review, 2021)
This paper appraised the necessary place of ethics in education. It analyse dissues of ethical concern in the key areas of education. Ethics, the moral philosophy, deals with issues and problems to do with nature of morality, and the principles that under lie moral judgement in every action ofan agent with compelling responsibility. Education being a task, achievement, process, concept and attendant practice necessarily requires the intervention of ethics to rid it of unacceptable properties for prudence and sanity. Every aspect in education practice is ethics bound, although the connection is tacit in some cases. However, argued are inherent ethical issues in the right to educate between state and learners, the right of parents and society in public education, rightness of educational organisation, interest of educational philosophies, queries about educational research, suitability of curriculum content and aptness of educational processes particularly teaching, training, drill, conditioning, coaching, indoctrination, initiation and imitation. It is concluded that education and ethics are necessarily related, and none of the contextual areas of education is free from ethical questions for its social and appetitive feature; hence the necessity of applying ethical apparatus.